The endothelial nitric oxide synthase gene G894T, glutathione S-transferase (GSTM1 and GSTT1) polymorphisms as a risk factor in the patient with nephrolithiasis - Mehdi, Wesen Adel; Mehde, Atheer Awad; Yusof, Faridah; Ahmad Raus, Raha; Resen, Ali Khudhair; Ghazali, Hamid (2019)
Background The genetic features indicate a crucial role in nephrolithiasis. The present study was aimed to investigate the role of Glutathione-S-transferase Mu (GSTM1), Glutathione-S- transferase Theta (GSTT1) and endothelial nitric oxide synthase (eNOs) gene polymorphism in nephrolithiasis.